IMPLEMENTASI STRATEGI KEPALA MADRASAH DALAM MENGHADAPI ERA REVOLUSI 4.0 - Ali Ubaidillah; Ami Latifah (UNISAN JURNAL, 2023)
The era of the industrial revolution 4.0 brought significant changes in various fields, including in the world of education. Madrasah heads as leaders of Islamic education institutions must be able to face challenges and take advantage of opportunities in the revolutionary era 4.0. This study aims to explore the implementation of the madrasa principal's strategy in dealing with the 4.0 revolution era. This research uses a qualitative approach with a single case study method at one madrasah in a big city. Data was collected through in-depth interviews with madrasa principals, teachers, administrative staff, and students, as well as participant observation and record keeping. The results of the study show that madrasa heads have carried out various strategies to deal with the 4.0 revolution era, including strengthening the quality of education, increasing teacher competence, using information and communication technology in learning, improving management quality, and developing extracurricular programs that are relevant to future needs. However, there are several challenges faced by school principals in implementing this strategy, including limited human and financial resources, lack of awareness and ability of teachers to integrate technology in learning, as well as limited infrastructure and adequate internet access. In facing the revolutionary era 4.0, madrasah principals need to continue to adapt to the changes that occur and take appropriate actions to strengthen the quality of education and the relevance of the curriculum to future needs. Principals also need to strengthen teacher competence and make optimal use of information and communication technology to increase learning effectiveness and efficiency. In addition, collaboration with various parties also needs to be carried out to strengthen support and expand the education network.